Maintaining Life Under Neoliberal Capitalism: A Case Study of Muslimah Laborers in Solo Raya, Indonesia - Yasih, Diatyka Widya Permata; Rakhmani, Inaya (Studia Islamika, 2024)
In the context of Muslim-majority Indonesia, we see the strengthening of Islamic piety as a response to the reorganization of people’s daily lives under neoliberal imperatives. Our study investigates how the often-overlooked Muslimah laborers in the historical locality of Solo Raya navigate their public and domestic spaces to fulfil distinctive gendered roles. They resort to organized labor movements to fight for workers’ rights and realize the imagination of working-class solidarity, while donning hijabs and negotiating curfews from their male guardians. They also play caregiving roles to parents, children, and husbands; filling the deficiency of basic social and health services they demand from the state, while ensuring security in the afterlife, which is not achievable in their material one. The pious common sense can impinge on the collective wills of the workers to challenge the neoliberal structures that shape experiences of marginalization. But it is no less meaningful in maintaining life (and being resilient) in an increasingly unfair socio-economic world.